2022
DOI: 10.1093/sleepadvances/zpac029.044
|View full text |Cite
|
Sign up to set email alerts
|

O045 Sleep management strategies among medical students

Abstract: Introduction Medical students are undertaking an intense curriculum, the stress of which may cause or worsen insomnia and depressive symptoms. We aim to investigate factors which might affect the sleep of medical students, and how they currently manage their sleep. Methods A brief online survey was sent to medical students, consisting of validated questionnaires, and questions related to sleep management strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…An analysis of one particular case showed that the prevalence of sleeplessness was 32.9% before examinations and dropped to 27.1% afterward. 4 Before the start of the yearly examinations in Pakistan, medical students' sleep health reveals a propensity for students to sleep less on exam days.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of one particular case showed that the prevalence of sleeplessness was 32.9% before examinations and dropped to 27.1% afterward. 4 Before the start of the yearly examinations in Pakistan, medical students' sleep health reveals a propensity for students to sleep less on exam days.…”
Section: Introductionmentioning
confidence: 99%